Reimagining Trauma: Japanese American Incarceration Reflected in Kenji by Mike Shinoda - Shofi Mahmudah Budi Utami; Muammar Kadafi (Journal of Language and Literature, 2023)
Trauma inherited by forbearers from those who had suffered racial injustice can endure so much consequence for later generations. Similarly, what had been affected to intergenerational Jews around the world about the Holocaust was, to an extent, repeated by Japanese Americans who had experienced incarceration during the World War II. This tragedy was recorded and reflected in several art and literary works including photography, short stories, and music. Interestingly, these eerie memories transmitted by the postgeneration or referred as ‘witness’ instead of ‘testifier’ (survivor) can be thoroughly seen present and well understood in such works. One of which is a song written by an American musician, Mike Shinoda, entitled Kenji. Therefore, this paper aims at figuring out on how this traumatic experience inhabited by the person who seemed to own the memories coming from someone else. Later in this study, the problem will be approached with postmemory by Frosh gradually by investigating constructive process in the lyrics of Kenji. In order to enhance discussion on this issue, the details of each line will be further analyzed with the concept of postmemory including memory, transmission and constructive process. As a result, the findings indicate that transmission of the trauma is reimagined through ‘actively’ constructive process by the songwriter as the ‘witness’ of the Japanese American incarceration. Rather than picturing the memory in similar context, the witness employs testimony in his creative reinvention to offer ‘new context’ in working through the trauma.